2017
DOI: 10.1007/s11938-017-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation: the Role of Metabolic Syndrome

Abstract: The long-term survival in liver transplant recipients (LTRs) is currently at an historical high level stemming from improvement in perioperative care, infection control, and immunosuppression medications. However, compared to the general population, LTRs have decreased survival. Metabolic diseases like hypertension, dyslipidemia, type 2 diabetes, and obesity are key determinants of long-term mortality in LTRs. The incidence and prevalence of these metabolic comorbidities is considerably higher in LTRs and like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Mari-Laryea et al showed that the cumulative incidence of major CVE was statistically more frequent in the post-MS group (MS: 8%, 24%, 29% at 1, 2 and 5-years follow-up vs 3%, 6 %, 10 % in non-MS) (p=0.003) (20). A metaanalysis showed that developing MS post-LT increased the risk of having a CVE by approximately 4 times compared to those without MS post-LT without affecting allcause mortality (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…Mari-Laryea et al showed that the cumulative incidence of major CVE was statistically more frequent in the post-MS group (MS: 8%, 24%, 29% at 1, 2 and 5-years follow-up vs 3%, 6 %, 10 % in non-MS) (p=0.003) (20). A metaanalysis showed that developing MS post-LT increased the risk of having a CVE by approximately 4 times compared to those without MS post-LT without affecting allcause mortality (3,23).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant reports show that the incidence rates of diabetes mellitus, hypertension, dyslipidemia, hyperuricemia, and obesity are 30%-40%[ 3 ], over 50%[ 4 ], 40%-66%[ 5 ], 14%-53%[ 6 - 9 ], and 18%-30%[ 10 , 11 ], respectively, and tend to increase with time after liver transplantation[ 12 ]. Metabolic disease is closely associated with the development of chronic kidney disease, infections, and cardiovascular diseases and greatly affects the quality of life and long-term survival of recipients[ 13 , 14 ].…”
Section: Forewordmentioning
confidence: 99%
“…Cardiovascular diseases are a major cause of long‐term morbidity and mortality after LT. This is hardly surprising, given the very high prevalence of risk factors among transplant recipients, who have obesity in 25%‐30% of cases; type 2 diabetes in 30%‐40%; and hyperlipidaemia in 45%‐70% . Overall, the diagnosis of metabolic syndrome can be established in 40%‐60% of LT recipients, judging from different studies .…”
Section: The Management Of Nutrition Before and After Transplantationmentioning
confidence: 99%
“…96,97 Overall, the diagnosis of metabolic syndrome can be established in 40%-60% of LT recipients, judging from different studies. 96,97 The onset of metabolic syndrome also seems to correlate inversely with the amount of physical activity. 98 The maximal rate of increase in fat mass usually coincides with the first year after LT.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation